Pengangkatan Perangkat Desa Dalam Hukum Islam - Harianto, Bambang; Siregar, Fatahuddin Aziz; Harahap, Ikhwanuddin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The purpose of this research is to know implementation of Law Number 6 of 2014 concerning the appointment of village officials in Gapuk Tua Village, Marancar District, South Tapanuli Regency in 2016, and a review of Islamic law on the implementation of Law Number 6 of 2014 concerning the appointment of village officials in Gapuk Tua Village. Marancar District, South Tapanuli Regency. The method used is a descriptive qualitative research method. The technique of collecting data in this research is through interviews, and observations. The results of this study concluded that the appointment of the Gapuk Tua Village Apparatus, Marancar District, South Tapanuli Regency as the implementation of Law Number 6 of 2014 concerning the appointment of village officials has not been fully implemented due to the lack of Village Apparatus requirements contained in the Act. The appointment of village officials through a process of direct appointment by the Village Head without an election process and deliberation with the residents and village officials. This is because there is an element of kinship between the village head and village officials. The review of Islamic law on the appointment of the Gapuk Tua village apparatus, Marancar District, South Tapanuli Regency has not fully implemented Islamic law, namely a leader must be fair and trustworthy.